Marketing / A Global Perspective - Chee Harold; Harris Rod (Pitman Publishing, 1993)
This book reflects the increasing integration of marketing and international marketing on a wide variety of courses. Preface, The Importance of Marketing, Understanding the Market, Developing Marketing Strategies, Marketing Challenges, Marketing Applications I: Services, Marketing Applications II: The Global Market, Marketing Implementation, Index.